2018
DOI: 10.1038/s42003-018-0206-4
|View full text |Cite
|
Sign up to set email alerts
|

In vivo multiphoton microscopy detects longitudinal metabolic changes associated with delayed skin wound healing

Abstract: Chronic wounds are difficult to diagnose and characterize due to a lack of quantitative biomarkers. Label-free multiphoton microscopy has emerged as a useful imaging modality capable of quantifying changes in cellular metabolism using an optical redox ratio of FAD/(NADH+FAD) autofluorescence. However, the utility of an optical redox ratio for long-term in vivo monitoring of tissue metabolism has not been robustly evaluated. In this study, we demonstrate how multiphoton microscopy can be used to monitor changes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
68
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 64 publications
(73 citation statements)
references
References 64 publications
3
68
0
Order By: Relevance
“…Lifetime measurements can distinguish between free and protein-bound forms of NAD(P)H and FAD, characterized by distinct molecular conformations that affect fluorescence quenching 49 . Previous studies have shown that metabolic autofluorescence imaging detects spatial and temporal changes in stromal cells across in vivo and 3D in vitro models 31,38,39,42,[50][51][52][53][54][55] . Thus, metabolic autofluorescence imaging of microscale 3D models was demonstrated to quantify metabolic activity and visualize macrophage heterogeneity within the 3D TME using primary human cancer, human cell lines, and mouse cell lines…”
Section: Introductionmentioning
confidence: 99%
“…Lifetime measurements can distinguish between free and protein-bound forms of NAD(P)H and FAD, characterized by distinct molecular conformations that affect fluorescence quenching 49 . Previous studies have shown that metabolic autofluorescence imaging detects spatial and temporal changes in stromal cells across in vivo and 3D in vitro models 31,38,39,42,[50][51][52][53][54][55] . Thus, metabolic autofluorescence imaging of microscale 3D models was demonstrated to quantify metabolic activity and visualize macrophage heterogeneity within the 3D TME using primary human cancer, human cell lines, and mouse cell lines…”
Section: Introductionmentioning
confidence: 99%
“…Measurement of intrinsic lifetime of NADH and FAD is emerging as a reliable technique for assessing cellular metabolism parameters in vitro 40 . NADH FLIM also enabled analysis of pharmacologically-induced alterations to mitochondrial metabolic processes from baseline cerebral metabolism in rat cerebral cortex 37 and metabolic changes at the front of wound re-epithelialization in diabetic and control mice 49 . This prompted us to apply protocol for measuring the spatial distribution of NADH in experimental models of tissue repair, as well as of cancer.…”
Section: Discussionmentioning
confidence: 99%
“…All tissue samples, including the biopsied tissue at day 0, were frozen in OCT at −80°C. The frozen wound tissue were sectioned into 30 μm thick samples, transferred to glass slides, and stained with H&E …”
Section: Methodsmentioning
confidence: 99%
“…On either day 3, 5, or 10 post-wounding, approximately 1 cm 2 of skin surrounding the wound was excised from each mouse following euthanasia. All tissue samples, including the biopsied tissue at day 0, were frozen in OCT at −80 C. The frozen wound tissue were sectioned into 30 μm thick samples, transferred to glass slides, and stained with H&E. 13…”
Section: Sample Preparationmentioning
confidence: 99%